A look at Aymara lexical studies and rules for the elaboration of a bilingual dictionary - Huayhua Pari, Felipe (2010)
Since 1583, when Spanish priests published a trilingual Doctrina Christiana, the Aymara language has had a long written tradition: dictionaries, vocabularies, dictionaries or grammars, if not all, have been bilingual (Spanish-Quechua, Spanish-Aimara, Portuguese-Guarani). The structure of a bilingual dictionary must conform to the standards of modern lexicography. Failure to do so may result in a defective product, since the preparation of a dictionary involves a careful treatment of grammatical and lexical aspects.